Comprehensive next-generation sequencing reveals low-grade fibromyxoid sarcoma of the vulva missed by morphological diagnosis: a case report - Tan, Shuang; Liu, Hongruo; Pan, Evenki; Liu, Siye; Zhang, Jiangyan; Wang, Jie; Wang, Ning (Frontiers in Medicine, 2024)
Low grade fibromyxoid sarcoma (LGFMS) is a rare soft tissue tumor composed of bland spindled cells in a variably fibrous to myxoid stroma. Its occurrence in the vulva region is rare, and thus it may not be always taken into account in the differential diagnosis. Here, we describe a 34-year-old woman presented with a right vulvar mass and underwent complete surgical excision. The final pathologic diagnosis revealedLGFMS of the vulva based on the morphological, immunophenotypic, and molecular genetic features. The patient has not experienced a local or metastatic recurrence after 9-months follow-up. Despite being rare, LGFMS of the vulva should be considered when making a diagnosis of vulvar lesions. We also report that the genetic testing by next-generation sequencing (NGS) represents a very useful tool for the differential diagnosis of LGFMS from its mimics. Moreover, we have reviewed the literature onLGFMS of the vulva and summarized the characteristics of the patients, providing assistance for the diagnosis of such patients. Most vulvovaginal LGFMS can be fully removed through surgery. However, ongoing monitoring over the long term is essential as local and/or distant spread can occur decades after the initial diagnosis.